A sacred mountain and the art of "Impression Management" - Carrasco Moraga, Anita (International Mountain Society, 2010)
The installation of a radio communication antenna on a sacred mountain, Mount Quimal, led to an interaction between a mining corporation and Atacameño people in northern Chile. The present article focuses on how language games that involve "over- and undercommunication" of information in this transactional event reflect the distribution of power in society.